(untitled) (REMUNOM, 2026)
The conflict between agent and principal is originally attributed to the separation between ownership and control. The realignment process occurs through corporate governance mechanisms, such as the monitoring exercised by the Board of Directors. However, when monitoring executives, board members, through disciplinary power, tend to orient conduct grounded in instrumental rationality. In highly institutionalized environments, however, this concept of efficiency may require reinterpretation. Thus, the present theoretical essay aimed to revisit the concept of instrumental efficiency within the agent–principal conflict in light of Institutional Theory. To this end, the disciplinary power of the Board of Directors, the precepts of instrumental rationality, and institutional factors such as “myths” and “ceremonies” are discussed. As a secondary empirical illustration, the relationship between a “myth” — the Corporate Sustainability Index — and instrumental efficiency criteria is presented, suggesting the relevance of an analytical revisiting of the aforementioned conflict.